Next-Generation Sequencing Identifies Transportin 3 as the Causative Gene for LGMD1F - Annalaura Torella; Francesco Mari; Margherita Mutarelli; Enrico Peterle; Francesca Del Vecchio Blanco; Rossella Rispoli; Marco Savarese; Arcomaria Garofalo; Giulio Piluso; Lucia Morandi; Giulia Ricci; Gabriele Siciliano; et al. (2013)
Limb-girdle muscular dystrophies (LGMD) are genetically and clinically heterogeneous conditions. We investigated a large family with autosomal dominant transmission pattern, previously classified as LGMD1F and mapped to chromosome 7q32. Affected members are characterized by muscle weakness affecting earlier the pelvic girdle and the ileopsoas muscles. We sequenced the whole exome of four family members and identified a shared heterozygous frame-shift variant in the Transportin 3 (TNPO3) gene, encoding a member of the importin-β super-family. The TNPO3 gene is mapped within the LGMD1F critical interval and its 923-amino acid human gene product is also expressed in skeletal muscle. In addition, we identified an isolated case of LGMD with a new missense mutation in the same gene. We localized the mutant TNPO3 around the nucleus, but not inside. The involvement of gene related to the nuclear transport suggests a novel disease mechanism leading to muscular dystrophy.